2022
DOI: 10.3389/fphar.2021.793607
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Leptin Levels in Patients With Eosinophilic Chronic Rhinosinusitis

Abstract: Background: Eosinophilic chronic sinusitis (ECRS) is a subtype of CRS with nasal polyps (CRSwNP) that is frequently comorbid with asthma. Notably, ECRS patients often show a high recurrence of NPs after surgical resection. Leptin is a hormone produced by adipocytes that has been implicated in airway inflammatory diseases. However, to date, the role of leptin in ECRS has not been investigated.Objective: To determine whether the serum levels of leptin are altered in patients with ECRS.Methods: In total, 40 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Leptin, a proinflammatory adipokine predominantly released from adipocytes, plays a key role in the regulation of food intake, body weight and energy metabolism. Several recent studies have reported that serum leptin levels increase in various inflammatory airway diseases, including COPD, asthma, AR, CRS, and nasal polyposis [1,2,5,[23][24][25]. Leptin receptors are expressed in bronchial epithelial cells, airway immune cells, and nasal epithelial cells [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, a proinflammatory adipokine predominantly released from adipocytes, plays a key role in the regulation of food intake, body weight and energy metabolism. Several recent studies have reported that serum leptin levels increase in various inflammatory airway diseases, including COPD, asthma, AR, CRS, and nasal polyposis [1,2,5,[23][24][25]. Leptin receptors are expressed in bronchial epithelial cells, airway immune cells, and nasal epithelial cells [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate leptin plays a role in the disease process of CRSwNP. Furthermore, Imoto et al, a study not included in the meta‐analysis due to missing data, observed that both eosinophilic CRS and noneosinophilic CRS patients had higher average serum leptin levels compared to healthy control patients without significant differences in BMI between cohorts 39 . Additionally, Song et al identified increased expression of leptin receptors in nasal polyps of patients with CRSwNP compared to the normal mucosa of healthy controls 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Imoto et al, a study not included in the meta-analysis due to missing data, observed that both eosinophilic CRS and noneosinophilic CRS patients had higher average serum leptin levels compared to healthy control patients without significant differences in BMI between cohorts. 39 Additionally, Song et al identified increased expression of leptin receptors in nasal polyps of patients with CRSwNP compared to the normal mucosa of healthy controls. 40 Taken together, leptin may play a role in CRS, and additional research is needed to investigate these associations to gain a better understanding of the influence of leptin on the inflammatory profile of CRS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although FESS is an effective treatment that rapidly alleviates clinical symptoms, a large proportion of CRSwNP patients require repeated surgery due to recurrence, particularly for those with a higher degree of tissue eosinophil infiltration [35][36][37]. Thereby, identifying biomarkers to early predict the recurrence of CRSwNP is extremely important and necessary.…”
Section: Discussionmentioning
confidence: 99%